Risk factors for hemorrhagic cystitis in children with severe beta-thalassemia after allogeneic hematopoietic stem cell transplantation - Dou, Hui-Hong; Luo, Jian-Ming; Zhao, Yan-Jun; Wang, Ji-Gan; Qin, Yuan-Han (Frontiers in Pediatrics, 2025)
PurposeTo investigate the risk factors for hemorrhagic cystitis (HC) in children with severe beta-thalassemia after allogeneic hematopoietic stem cell transplantation (allo-HSCT).MethodsThe clinical data of 152 children under the age of 15 who underwent allo-HSCT between January 2011 and December 2021 were retrospectively analyzed. The incidence of HC and related variables were evaluated using univariate analysis. Variables with statistical significance (P < 0.05) were included in a multivariable logistic regression model to identify independent risk factors for HC.ResultsAmong the 152 children, 42 developed HC, with an incidence rate of 27.63%. The median onset time of HC was 25 days (IQR: 10–38.75 days). Univariate analysis indicated that older transplantation age, elevated pre-transplant serum ferritin levels, cytomegalovirus (CMV) infection, and prolonged neutrophil engraftment time were associated with HC occurrence (P < 0.05). Multivariable logistic regression further confirmed that older transplantation age (OR 1.236, 95% CI: 1.031–1.531, P = 0.033), elevated pre-transplant ferritin levels (OR 1.053, 95% CI: 1.028–1.086, P < 0.01), CMV infection (OR 11.522, 95% CI: 2.912–76.345, P = 0.002), and prolonged neutrophil engraftment time (OR 1.385, 95% CI: 1.109–1.793, P < 0.01) were independent risk factors for HC.ConclusionOlder transplantation age (>5.95 age years old), elevated pre-transplant serum ferritin levels, CMV infection, and delayed neutrophil engraftment are independent risk factors for HC in children with severe beta-thalassemia after allo-HSCT. Early identification and intervention for these risk factors are crucial in reducing the incidence of HC.